STRENGTHENING THE BORDER CONTROL MANAGEMENT SYSTEM IN THE FRAMEWORK OF SUPERVISION OF FOREIGNERS THAT HAS BEEN DENIED TO ENTER INTO INDONESIA - Rendji Sola Gracia Silalahi (TEMATICS: Technology ManagemenT and Informatics Research Journals, 2020)
This research discusses the strengthening of Border Control Management (BCM) system in the context of monitoring foreigners who have been refused entry to Indonesian territory. The Border Control Management system is the border management system that aims as a regional surveillance management system at state borders which aims to handle all forms of settlement of activities of crossing people both entering and leaving Indonesian territory, but to assist the supervision of foreigners who have entered Indonesian territory. It is deemed necessary to strengthen the system Border Control Management to assist immigration officials and immigration officers in detecting these foreigners. The writing method used in this final report is descriptive qualitative research a method by conducting interviews and surveys to the Immigration Checkpoints of Kualanamu International Airport and the Class 1 Special Immigration Office of TPI Medan. The results of the study show that by strengthening the system it Borders Control Management is felt that it can help immigration officers in making decisions.